Photographs, Manzanar, 1942-43 - Lloyd Linn::::::photographer::: (1942)
Photograph of friends posed in front of a car, with the camp police station in the background. Inscription on back of photograph: "Lorraine Paulson, Miriko Nagahama, Honey Toda, Wilda Johnson, Betty Salzman. Photographer Lloyd Linn, Wilda's friend. Manzanar, CA 6-21-42". Accompanying note reads: "The Photo @ Manzanar, 6-21-42: at the entry to the camp. The building in the background has a sign: Police Station. As I recall, at that time that was the only location we could take a picture. Betty Liebscher".